1993
DOI: 10.1016/s0248-4900(05)80170-4
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary studies about novel strategies to reverse chemoresistance to adriamycin regarding glutathione metabolism, peroxisomal and extraperoxisomal hydroperoxide and valproic acid metabolic pathways

Abstract: The present work was aimed at defining novel strategies to reverse chemoresistance to anticancer drugs, especially by interfering with cellular glutathione metabolism, peroxisomal and/or extraperoxisomal hydroperoxide metabolic pathways. Preliminary results are presented about molecules we demonstrated to be capable of interfering with hydrogen peroxide metabolism in cells. Prior to describing these molecules, a short overview of glutathione and free radical metabolic pathways is presented as well as a rapid p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Four metabolic pathways have been found: glucuronidation,/?-oxidation, co-oxidation, (co-1)-oxidation and the metabolism of valproate appears to be complex in regard to the natural fatty acids normally absorbed in man. Vamecq et al (1993) reported that the coenzyme A esters of valproic acid and related metabolites are handled by a peroxisomal/?-oxidation pathway distinct from fatty acid and bile acid/?-oxidation routes. In this way, VPA and related metabolites have the capacity to induce higher cellular hydrogen peroxide (H20~) levels because of their ability to act as substrates for H202-generating oxidases (Van den Branden & Roels, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Four metabolic pathways have been found: glucuronidation,/?-oxidation, co-oxidation, (co-1)-oxidation and the metabolism of valproate appears to be complex in regard to the natural fatty acids normally absorbed in man. Vamecq et al (1993) reported that the coenzyme A esters of valproic acid and related metabolites are handled by a peroxisomal/?-oxidation pathway distinct from fatty acid and bile acid/?-oxidation routes. In this way, VPA and related metabolites have the capacity to induce higher cellular hydrogen peroxide (H20~) levels because of their ability to act as substrates for H202-generating oxidases (Van den Branden & Roels, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…There are a number ofcytosolic mechanisms for eliminating toxic reagents, including the enhanced activity of the pentose phosphate shunt (57) and changes in glutathione metabolism (58)(59)(60). Enzymes involved in both of these pathways are modified in some MDR cell lines.…”
mentioning
confidence: 99%
“…Superoxide, hydrogen peroxide, and hydroxyl radicals are reactive oxygen species which can form in the reduction of oxygen by the anthracycline semiquinones. The Fe(Il)-doxorubicin complex is able to catalyze the oxidation of thiol by O2, promoting the oxidative destruction of macromolecular targets (13,14,16,17,(58)(59)(60).…”
mentioning
confidence: 99%